Partisipasi Mahasiswa dalam Pemilihan Ketua dan Wakil Ketua Ikatan Mahasiswa Pendidikan Pancasila dan Kewarganegaraan Universitas Jambi sebagai Penerapan Demokrasi Politik - Amonita, Oci; Anderson, Irzal; Hajri, Priazki (Journal of Civic Education, 2023)
This study investigates the factors contributing to the limited engagement of students enrolled in Pancasila and Civic Education programs at Universitas Jambi in organizational elections. Employing a descriptive qualitative approach, the research utilizes interviews, observations, and documentation for data collection, with subsequent analysis involving data collection, reduction, presentation, and verification. Key informants include supervisory lecturers, student organization leaders, and Pancasila and Civic Education students. Findings reveal persistently low participation among Civics students in the 2023 student organization elections, attributed to various implementation challenges such as inadequate adherence to governing regulations, insufficient preparedness of the organizing committee, external interference, and conflicts between students and faculty members. Contributing factors to low participation encompass conflicting interests, political strategies, student awareness levels, communication effectiveness, geographical distance, external commitments, and perceived lack of impact or benefit. The study recommends increased efforts by the governing body to enhance student engagement through proactive social media campaigns and urges Pancasila and Civics Education students to heighten their awareness and involvement in electoral processes.